1992
DOI: 10.1182/blood.v80.3.688.bloodjournal803688
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant glycosylated human interleukin-6 accelerates peripheral blood platelet count recovery in radiation-induced bone marrow depression in baboons

Abstract: This report was aimed at confirming the potential clinical use for a genetically engineered glycosylated human interleukin-6 (rhIL-6) in hematopoiesis. Its tolerance and efficacy were assessed on hematopoietic restoration after neutron radiation-induced bone marrow injury on baboons, which represent an adequate model of parallelism for studying hematology in the human. The particular neutron radiation absorption pattern in the body allows the preservation of underexposed bone marrow areas that mimics an autotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These data suggested that IL-6 generated "thrombopoietin"-like activity but not "megakaryocyte-CSF"like activity (Stahl et al 1991;Geissler et al 1992;Herodin et al 1992;MacVittie et al 1994;Farese et al 1995). The cynomolgus macaque was selected as the model based on the similarities between simian and human hematopoiesis (Welte et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested that IL-6 generated "thrombopoietin"-like activity but not "megakaryocyte-CSF"like activity (Stahl et al 1991;Geissler et al 1992;Herodin et al 1992;MacVittie et al 1994;Farese et al 1995). The cynomolgus macaque was selected as the model based on the similarities between simian and human hematopoiesis (Welte et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…This allowed comparison to several studies that used combinations of IL-6 with the same cytokines in the rhesus macaque. The rhesus macaque studies used relatively higher, more myelosuppressive, sublethal, bilateral TBI, with equivalent results (Stahl et al 1991; Herodin et al 1992; MacVittie et al 1994). The other study assessed the efficacy of rhGH to mitigate myelosuppression after low-dose TBI and showed a marginal hematopoietic response (Chen et al 2010).…”
Section: Primary Studies Cynomolgus Macaquesmentioning
confidence: 99%